Survival comparisons of intensive vs. conventional hemodialysis: Pitfalls and lessons. Issue 1 (20th April 2017) - Miller, Amanda J.; Perl, Jeff; Tennankore, Karthik K.
Abstract: The optimal dose of hemodialysis (HD) has not yet been established. As a means of better approximating the physiology of native kidney function, there has been a growing interest in intensive HD (an increase in dialysis frequency and/or duration). Although many studies have demonstrated a survival benefit with intensive dialysis, results have been conflicting. This controversy stems from the challenges of randomizing patients to conventional vs. intensive HD modalities and, therefore, the reliance on observational comparisons that have been limited by varying definitions for intensive dialysis, differences in dialysis location and prescription, unavoidable treatment selection bias, and a potential lack of generalizability. This review will discuss the pitfalls and complexities surrounding survival comparisons with intensive HD, and identify important directions for future study.